THE EDDY CURRENT DIAGNOSTICS METHOD FOR THE PLASTICALLY DEFORMED AREA SIZES EVALUATION IN NON-MAGNETIC METALS - Marchenkov, Artem Yurievich; Khvostov, Andrey Alexandrovich; Slavinskaya, Ekaterina Andreevna; Zhgut, Daria Alexandrovna; Chernov, Dmitriy Vitalievich (Journal of Applied Engineering Science, 2020)
The aim of this research is to reveal and determine the sizes of plastically deformed areas in metallic non-magnetic materials with the eddy current method. The manuscript contains computational studies to assess the feasibility of using the eddy current method to determine the size of the plastically deformed areas in the metal. The authors developed a two-dimensional mathematical model of the interaction of the electromagnetic field with the control object. The model included poly-harmonic field excitation in a locally deformed plate, and the deformation was modeled in the form of plastically deformed areas under the indents obtained by the ball indentation. The developed model helped to establish the correlation dependencies and linked the informative parameters of the eddy current method with the size of the metal’s plastically deformed zone. The authors obtained the calibration curve for copper, the values of which allowed to determine the factual sizes of the plastically deformed area.